New approaches to the Begg technique: Part I - Qualitative Aspects - Mollenhauer Barry (Sciendo, 1987)
The development of new materials and wires has allowed the creation of new mechanisms. These include new aligning and torquing wires which provide gentler pressures yielding rapid tooth movement. Different finishing systems are available with different purposes. There has arisen the need to formalise treatment planning using a Visualised Treatment Objective and to document post-treatment changes cephalometrically. These various factors dictate a new look at traclitional Begg teaching.